EngOpt 2018 Proceedings of the 6th International Conference on Engineering Optimization 2018
DOI: 10.1007/978-3-319-97773-7_90
|View full text |Cite
|
Sign up to set email alerts
|

A Gradient-Based Strategy for the Optimization of Stiffened Composite Structures Subject to Multiple Load Cases and Multiple Failure Criteria

Abstract: This work aims at investigating the applicability of the level-set based thickness optimization method, earlier proposed by the authors, to a realistic structure. The design has to have sufficient stiffness and strength while the structural mass is minimized. The concerned composite structure is subjected to multiple load cases. The proposed method guarantees the fulfillment of the design guidelines, namely symmetry, covering ply, disorientation, percentage rule, balance, and contiguity of the layup. The stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This method aims at optimizing the stacking sequences and thickness distribution of large-scale composite structures considering the design rules and manufacturing guidelines. In [21], it is shown that this proposed method can be successfully applied to the optimization problem of the skins of an aircraft wing, in which multiple load cases and constraints (such as buckling and strain) are applied. In the present research, both the wing-level and rib-level optimization problems employ the level-set strategy for the optimization of composite structures, previously introduced in [17].…”
Section: B Motivation and Aim Of The Present Researchmentioning
confidence: 99%
“…This method aims at optimizing the stacking sequences and thickness distribution of large-scale composite structures considering the design rules and manufacturing guidelines. In [21], it is shown that this proposed method can be successfully applied to the optimization problem of the skins of an aircraft wing, in which multiple load cases and constraints (such as buckling and strain) are applied. In the present research, both the wing-level and rib-level optimization problems employ the level-set strategy for the optimization of composite structures, previously introduced in [17].…”
Section: B Motivation and Aim Of The Present Researchmentioning
confidence: 99%